Do Short-Term Real Estate Investors Outperform the Market?. Issue 2 (3rd April 2022) - Wong, Siu Kei; Deng, Kuang Kuang; Chau, Kwong Wing
Abstract: Some real estate investors engage in short-term trading in spite of the high transaction costs that this involves. While previous studies have identified various incentives that encourage short-term investors to engage in these practices, there has, to date, been little investigation into the influence of different market conditions over their performance. Based on real estate transaction data from Hong Kong, this study finds that buying and reselling within three months produces, on average, a gross return of 6% above the market. Three economic conditions are shown to be favorable to their performance: 1) comparable transactions are scant; 2) prices are more dispersed; and 3) market prices go down. Further analysis reveals that these short-term investors make a greater profit from purchases than from resales. While it is beyond the scope of this study to pin down the strategy adopted by each investor, the results are consistent with a "search" explanation, according to which, short-term investors behave as if they were arbitrageurs capable of exploiting the valuation spread between buyers and sellers.